Molar-incisor hypomineralization: the importance of differential diagnosis to institute adequate treatment for patients affected by this condition (Research, Society and Development, 2021)
This study proposes to review the literature about the Molar-Incisor Hypomineralization (MIH) to identify the clinical characteristics and know how to differentiate them from other enamel anomalies to promote the correct diagnosis and treatment of these cases. An exploratory narrative bibliographic review was carried out through consultations in the SciELO, LILACS, PubMed, and BVS databases, based on articles published in Portuguese and English, without restriction to the year of publication. The 22 studies selected for this review, evaluated MIH as a qualitative defect in enamel development, with a not so defined systemic etiology, in which it is possible to observe chromatic or structural changes in the enamel of first molars and permanent incisors. Teeth affected by MIH have an enamel with well-defined opacity, with a white, yellow, or brown coloration, visually identified as an abnormality in their translucency. Soon after the eruption of the tooth element, episodes of post-eruptive fractures are commonly seen due to the characteristics of the enamel being porous, being fragile, and susceptible to fracture. Frequently, the clinical features of MIH can be confused with other developmental defects of the enamel, thus hindering the early diagnosis and an adequate intervention for its treatment. Therefore, knowledge about this anomaly allows the professional to establish a differential diagnosis, which will favor an effective treatment plan, thus avoiding tooth loss and the establishment of a condition of well-being and comfort for the patient affected with this condition.